The politics of multiculturalism : pluralism and citizenship in Malaysia, Singapore, and Indonesia - Hefner, Robert W., 1952- (Honolulu : University of Hawai'i Press, 2001)
Few challenges to the modern dream of democratic citizenship appear greater than the presence of severe ethnic, religious, and linguistic divisions in society. With their diverse religions and ethnic communities, the Southeast Asian countries of Malaysia, Singapore, and Indonesia have grappled with this problem since achieving independence after World War II. Each country has on occasion been torn by violence over the proper terms for accommodating pluralism. Until the Asian economic crisis of 1997, however, these nations also enjoyed one of the most sustained economic expansions the non-Western world has ever seen. This timely volume brings together fifteen leading specialists of the region to consider the impact of two generations of nation-building and market-making on pluralism and citizenship in these deeply divided Asian societies. Examining the new face of pluralism from the perspective of markets, politics, gender, and religion, the studies show that each country has developed a strikingly different response to the challenges of citizenship and diversity. The contributors, most of whom come Southeast Asia, pay particular attention to the tension between state and societal approaches to citizenship. They suggest that the achievement of an effectively participatory public sphere in these countries will depend not only on the presence of an independent "civil society," but on a synergy of state and society that nurtures a public culture capable of mediating ethnic, religious, and gender divides. The Politics of Multiculturalism will be of special interest to students of Southeast Asian history and society, anthropologists grappling with questions of citizenship and culture, political scientists studying democracy across cultures, and all readers concerned with the prospects for civility and tolerance in a multicultural world
The culture and practice of pluralism in postcolonial Malaysia / Abdul Rahman Embong -- Social pluralism in Singapore / Chua Beng Huat and Kwok Kian-Woon -- Social resources for civility and participation: the case of Yogyakarta, Indonesia / Mohtar Mase̤d, S. Rizal Panggabean, and Muhammad Najib Azca -- Boundaries and beyond: whither the cultural bases of political community in Malaysia? / Sumit K. Mandal -- Corporate pluralism: Singapore Inc. and the Association of Muslim Professionals / Sharon Siddique -- Where has (ethnic) politics gone? The case of the BN non-Malay politicians and political parties / Francis Loh Kok Wah -- The redefinition of politics and the transformation of Malaysian pluralism / Shamsul A.B. -- What Islam, whose Islam?: Sisters in Islam and the struggle for women's rights / Zainah Anwar -- Gender and pluralism in Indonesia / Siti Ruhaini Dzuhayatin -- Mirroring the past or reflecting the future?: class and religious pluralism in Indonesian labor / Vedi R. Hadiz -- Greens in the rainbow: ethnoreligious issues and the Indonesian armed forces / Hermawan Sulistiyo.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Cultural pluralism -- Malaysia; Cultural pluralism -- Singapore; Cultural pluralism -- Indonesia; Multiculturalism -- Malaysia; Multiculturalism -- Singapore; Multiculturalism -- Indonesia; Citizenship -- Malaysia; Citizenship -- Singapore; Citizenship -- Indonesia; Diversité culturelle -- Malaisie; Diversité culturelle -- Singapour; Diversité culturelle -- Indonésie.; Multiculturalisme -- Malaisie; Multiculturalisme -- Singapour; Multiculturalisme -- Indonésie.; 89.51 political sociology; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Citizenship; Cultural pluralism; Multiculturalism; Indonesia; Malaysia; Singapore; Multikulturelle Gesellschaft; Politik; Singapur; Indonesien; Malaysia; Multiculturele samenlevingen; Plurale samenleving; Burger en overheid; Beleid; Relações étnicas e raciais -- Sudeste asiático.; Multiculturalismo -- Malásia;singapura;indonésia.; Antropologia cultural e social -- Sudeste asiático.; Aufsatzsammlung